Neutrino-Induced Coherent π⁺ Production in C, CH, Fe, and Pb at ⟨Eν⟩ ∼6 GeV - Ramirez, M.A.; Akhter, S.; Ahmad Dar, Z.; Akbar, F.; Ansari, V.; Ascencio-Sosa, M.V.; Athar, M.; Bashyal, A.; Bellantoni, L.; Bercellie, A.; Betancourt, M.; Bodek, A.; et al. (American Physical Society, 2023)
MINERvA has measured the νμ-induced coherent π⁺ cross section simultaneously in hydrocarbon (CH), graphite (C), iron (Fe), and lead (Pb) targets using neutrinos from 2 to 20 GeV. The measurements exceed the predictions of the Rein-Sehgal and Berger-Sehgal PCAC based models at multi-GeV νμ energies and at produced π⁺ energies and angles, Eπ > 1 GeV and θπ < 10°. Measurements of the cross-section ratios of Fe and Pb relative to CH reveal the effective A scaling to increase from an approximate A¹ˡ³ scaling at few GeV to an A²ˡ³ scaling for Eν > 10 GeV.
Keywords: Physics; Neutrino; Production (economics); Particle physics; Nuclear physics; https://purl.org/pe-repo/ocde/ford#1.03.03